Monopolistic supply of sorting, inequality, and welfare. (3rd June 2021) - Windsteiger, Lisa
Abstract: Why is an increase in income inequality often accompanied by an increase in socioeconomic segregation? And what are the welfare implications of this comovement? This paper uses a theoretical model to analyze the relationship between income inequality and socioeconomic segregation. It shows that rising inequality can trigger sorting according to income, as a monopolist's profits from offering sorting increase with income inequality. It also examines the relationship between sorting and social welfare and shows that profit‐maximizing sorting patterns are not necessarily optimal from a welfare perspective. In fact, for a broad field of income distributions (monopolist) profits increase with inequality, while at the same time total welfare from sorting decreases.